The capillary index score: rethinking the acute ischemic stroke treatment algorithm. Results from the Borgess Medical Center Acute Ischemic Stroke Registry. (19th January 2012) - Al-Ali, Firas; Jefferson, Anne; Barrow, Tom; Cree, Travis; Louis, Susan; Luke, Kim; Major, Kevin; Nemeth, Daniel; Smoker, Sandy; Walker, Sarah
Abstract : Background: Despite increased recanalization rates in the treatment of acute ischemic stroke, the percentage of patients with a good clinical outcome of all those treated has not risen above 50%. This 50% barrier may be broken by improving the criteria for treatment selection. This study investigated the addition of the capillary index score (CIS), a new index for assessing remaining viable tissue in the ischemic area, to the existing criteria. Methods: The Borgess Medical Center Ischemic Stroke Registry is a non-randomized single-center single-operator registry of consecutive subjects admitted for intra-arterial treatment of acute ischemic stroke. The CIS was calculated from a pre-intervention catheter cerebral angiogram in subjects with internal carotid artery (ICA) or middle cerebral artery (MCA) (M1) occlusion. Thrombolysis In Myocardial Infarction (TIMI) 2 or 3 was considered successful recanalization. A modified Rankin Scale (mRS) of 0–2 at 3 months was considered a good outcome. Results: ICA or MCA (M1) occlusion was found in 46 of 58 consecutive patients treated by the same operator. Recanalization was successful in 72% of patients and 27% had a good outcome. CIS was available for 26 patients; 42% were favorable (2 or 3) and 58% were poor (0 or 1). A good outcome was found only in the favorable CIS group (p=0.0148). Successful recanalization (p=0.0029) and time from ictus to revascularization (p=0.0039) predicted a good outcome. Of patients with favorable CIS and TIMI 3, 83% had a good outcome. Conclusions: Favorable CIS and recanalization were strong predictors of a good outcome. By using this new index as an adjunct to other criteria, the CIS may improve patient selection and help break the 50% barrier.